Ethnographic Reflections on Nationalism and Interfaith Dialogue in the Three-Faith Tourism Village - Rizki Budhi Suhara; Nurul Chamidah; Johan Johan; Dina Kholis Aziza; Nurhidayah Nurhidayah; Wildan Aflah Nabil; Eef Sayfudin; Nanang Sunadi Arta (Universitas Darussalam Gontor, 2025)
This study analyzes the Jamblang mural attraction located in the Old Town Area of Jamblang, Jamblang Village, Jamblang District, Cirebon Regency known as the Three-Faith Tourism Village as a complex communication event within the framework of nationalism. The mural attraction, created collaboratively by students, artists, and local residents, retells the history of communal existential crises (1845–1889) leading up to the turning point of recovery in 1900, focusing on the restoration of Vihara Dharma Rhakita. Its primary purpose is to revitalize the forgotten Chinatown area, provide historical education, and deeply instill the values of tolerance and national unity. This qualitative research employs the framework of Ethnography of Communication and the Triadic Semiotic analysis of Charles Sanders Peirce to examine the visual messages and surrounding social practices. The semiotic analysis reveals that the mural’s iconography (Representamen), depicting collective suffering and recovery, produces an Interpretant of nationalism. This nationalism can be understood as the collective memory of resilience within a multireligious community, where harmony becomes the essence of local patriotism. This notion is reflected through particular signs and symbols depicted in the mural, which represent the shared struggle and unity of different faiths. Considering Indonesia’s historical concept of Nasakom, such expressions suggest how ideological and social classifications may still shape local narratives of nationalism. The meaning and intention behind these representations were also conveyed by the interviewed informants, indicating that the interpretation of the mural should be grounded in their perspectives. The application of Dell Hymes’ SPEAKING model integrates semiotic findings with real communication practices. It was found that the mural’s strategic placement in front of the Vihara (Setting) and the inclusive interfaith collaboration (Participants) explicitly support the Ends of promoting National Tourism. The social interaction norms (Norms) are directed toward displaying harmony to visitors, while selfie-taking activities (Act Sequence and Genre) function as an adoption of this collective narrative into personal digital identity. This study concludes that the Jamblang mural successfully transforms local history into a visual lingua franca (Instrumentalities) that effectively fosters national resilience education and tourism village branding, mitigating the challenges of spatial and economic degradation.